Pendidikan Perempuan Dalam Perspektif Feminisme Dan Islam - Aisjah Aisjah (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2017)
Education plays an important role in improving the quality of life of a person, including women. In pre-Islamic times, women in the world are only used as sexual exploits of men’s sexual desires, and are under male power. There is no education or knowledge, except as a devotee for men. Modernization has not been able to reduce the equal rights of women with men. Discrimination against women has spawned struggles against women’s rights, and encourages the birth of feminism. But these movements do not always have a positive impact but also generate perceptions and build a paradigm that corners Islam. The purpose of this study is to describe women’s education and its role in feminist and Islamic perspectives. This research tries to interpret the thoughts of feminist figures, Alquran, Hadith, and thoughts of Islamic leaders on women’s education. Interpretation is done by considering the values contained in the thoughts of feminism figures (from the western or Indonesian aspect), and connecting with the concept of Islam (in the Qur’an, Hadith, and the thinking of Islamic figures). The Western Feminist Movement gave birth to lesbian, heterosexual, and androgynous groups, as well as the demands of equality in terms of wages, and types of work in all fields. The demand for educational equality is used for “liberation of women”, interpreted as the liberation of the role of mother and wife, and dominates the demands of public roles, even women’s education is oriented to economic improvement, as well as sex. Islam as a universal religion has provided a happy life, whose achievements depend on the educational process it undergoes, because education is the key to opening the path of human life. Women’s education is needed to equip women with wide knowledge both worldly and ukhrawi. The more knowledgeable, the women will be able to perform their roles both as mothers, and wives, and Islam gives women the right to play a role in the public, meaning that women as members of the community have the potential to participate actively in the development of community life.